From New Netherland to ‘New Zeeland’ - Krabbendam, Hans (BMGN - Low Countries Historical Review, 2013)
Evan Haefeli’s book (New Netherland and the Dutch Origins of American Religious Liberty (Philadelphia 2012)) corrects the wide-spread belief that the Dutch in colonial America were responsible for introducing religious tolerance in the New World. Instead, he shows convincingly how the concept of tolerance as an ideal was never the plan, but the practical outcome of a process of dynamic power relationships which turned out to be more tolerant than most other nations. He explains how this idea of the Dutch as the founders of tolerance emerged and how events in the Dutch Republic and its colonies shaped practices and policies in New Netherland. This book is instructive about the impact of national boundaries on religious loyalties in the early modern period and contributes to the current debate about religious tolerance.